Crown and regeneration responses to silviculture systems in Pine and Sal forests: preliminary results from silviculture trials in Mid-hills Nepal - Cedamon, E.; Paudel, G.; Basyal, M.; Nuberg, I.; Paudel, N. (Banko Janakari, 2018)
Silviculture trial plots were established in Kavre and Lamjung districts by the EnLiFT Project (Enhancing livelihoods and food security through improved agroforestry and community forestry in Nepal) to examine stand response to selected silviculture systems – uniform shelterwood, selection system, and negative thinning and as a showcase to forest users for these silviculture systems. This paper analyses the extent of canopy gaps on these trial plots after one-year of application of silviculture treatments and regeneration development. Using crown photographs, crown cover was estimated and compared between silviculture systems. The analysis showed that rigid silviculture systems like shelterwood and selection systems created canopy gap larger than negative thinning in Pine plantations and the rate of natural regeneration was directly related with the canopy gap. However, in Shorea robusta-Castanopsis- Schima (Sal-Katus-Chilaune) forest, negative thinning created canopy gap larger than selection system due to removal of 4-D trees, majority of trees were Schima wallichii (Chilaune), which typically have large spreading crown. Although, it may be too early to conclude the relationship between regeneration development and canopy gap from the trial plots, it became clear that silviculture operations have significant role in promoting higher regeneration. Selection and shelterwood systems are better than current silviculture regime represented by negative thinning in this study. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page: 98-103